COMPARISON BETWEEN STANDARD ULTRASONOGRAPHY, ANGLE CONTRAST ULTRASONOGRAPHY, AND MAGNETIC RESONANCE IMAGING CHARACTERISTICS OF THE NORMAL EQUINE PROXIMAL SUSPENSORY LIGAMENT. Issue 5 (29th May 2013) - Werpy, N.M.; Denoix, J.M.; McIlwraith, C.W.; Frisbie, D.D.
Abstract : Previous studies have proposed that standard ultrasonography may not adequately represent the pertinent anatomic characteristics of the equine proximal suspensory ligament. The purpose of the study was to compare the use of standard ultrasonography, angle contrast ultrasonography, MRI, and histology for identification of the anatomic characteristics of the normal equine suspensory ligament in the forelimb. Horses free from forelimb lameness with no palpable abnormalities in the region of the suspensory ligament were included in the study. The proximal suspensory ligaments in 20 forelimbs were examined using the standard ultrasound technique, angle contrast ultrasound technique, and MRI, followed by histologic evaluation. Total transverse (cross‐sectional) area of the proximal suspensory ligament was estimated using the standard ultrasound and the angle contrast ultrasound techniques, MRI, and histologic sections for the following parameters: total area of the ligament, ligament fibers, muscle, and fat. The proximal suspensory ligament lobe size and tissue distribution were compared and subjectively graded (0–4) for asymmetry. Subjectively, angle contrast ultrasound technique improved differentiation of fibers from the remaining tissue types and allowed identification of the peripheral ligament margin. There was no significant difference in asymmetry scores between modalities. The asymmetry scores of the right and left forelimbs were significantly different with both ultrasound and MRI, based on the level of measurement. The angle contrast ultrasound technique has limitations compared to MRI. However, it provides additional diagnostic information that is not available with the standard ultrasound technique.